THE RESPONSIBILITIES OF THE NOTARY THIRD PARTY SERVICES (REALTOR) TO GET CLIENTS - Gafur, Abdul; Pramono, Budi; Sunardi, Sunardi (Universitas Islam Malang, 2022)
Notary is a profession with a very noble position (nobile officium). because of why a notary is burdened with obligations and prohibitions to obey. sometimes notaries are often negligent in their actions, this is triggered, by the increasing number of new notary graduates, giving rise to unhealthy competition however. This competition sometimes takes the form of ethical violations committed by a notary, such as using the services of other parties (brokers) to get clients. so this needs to be examined further regarding